Comparison of Opuntia Ficus-Indica and Punica Granatum Oil in Healing Skin Wounds - EY Al-Zubaidy; B Abdal Ghani (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Chemical drugs are effective for wound healing, but herbal drugs with relative safety mainly reduce the adverse effects of chemical drugs in wound healing. The use of Opuntia ficus-indica oil and punica granatum oil as a natural remedy is prevalent due to the perceived beneficial properties. The aim of the present study is to compare the impact of “opuntia oil” and “punica oil” separately and in combination on skin wound healing. Methods: This triple-blind clinical trial included 32 male adult New Zealand rabbits with a mean weight ranging from 1.5 to 2.0 Kg. Four circular standardized wounds were created on the dorsal region of each rabbit using a sterile biopsy punch with a diameter of 8 mm. The wounds intentionally left uncovered and the wound on the upper right side was not treated. The wound located on the upper left side was subjected to treatment with Opuntia ficus-indica oil. Punica granatum oil was used to treat a wound located on the lower right side. The lower-left-side wound was ultimately treated with a mixture of opuntia ficus-indica oil and punica granatum oil. The three experimental groups received daily treatment including topical application of 10 µl of opuntia ficus-indica oil, punica granatum oil, or a combination of these two oils, and wound healing in the groups was compared on days 1, 3, 7, and 14. Findings: Wound healing in experimental groups showed a significant difference compared to the control group. The combination group exhibited the greatest mean value of wound contraction at day 14, reaching 84.6% at the experimental site. The analysis of inflammatory cell count revealed that the experimental groups treated with punica granatum oil exhibited the greatest mean values, reaching 68% on day one. Additionally, the mean values of epithelial thickness rose with time in all groups, with the combination group displaying a mean value of 38.5±3.5 um on day 14. There were notable differences between the control and experimental groups throughout all healing phases. Conclusion: The results of the study showed that both opuntia ficus-indica oil and punica granatum oil are effective in wound healing compared to the control groups.